Peningkatan Minat Dan Hasil Belajar Subtema Kegiatan Di Sore Hari Melalui Whatsapp Group Dengan Pendampingan Orang Tua: Pada Siswa Kelas I SD Negeri Kajar Semester 1 Tahun Pelajaran 2021/2022 - Tasmini, Tasmini (Universitas Cokroaminoto Yogyakarta, 2022)
This classroom action research aims to increase interest and learning outcomes using the whatsapp group application in the subject of the activity sub-theme in the afternoon of first graders at SDn Kajar. The research subjects were 26 students. Data collection techniques using the method of test, observation and documentation. The data validation technique uses source triangulation. Data analysis used descriptive qualitative technique. The students' learning interest in the initial condition was 9 students or 34.62%, to 65.38% or 17 students, and 92.31% or 24 students in the second cycle. The average value of the initial conditions was 59.62 increased to 68.33, and 78.08 in the second cycle, while the level of mastery learning from 8 students or 30.77% to 16 students or 61.54% and 23 students or 88, 46% in the second cycle. This increase in learning outcomes can not be separated from the skills of teachers and students' interests. Referring to the research indicators, namely 85% of students experienced individual learning completeness 70, the research was declared successful.